1973
DOI: 10.1128/aac.3.4.478
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Pharmacokinetics of BB-K8 and Kanamycin in Dogs and Humans

Abstract: Comparative studies in beagle dogs suggested that the pharmacokinetic profiles of BB-K8 and kanamycin are similar. After intravenous (iv) administration to dogs, BB-K8 and kanamycin were rapidly distributed in plasma and tissue fluids; their "apparent" volumes of distribution comprised approximately 23% of the total body volume. Like kanamycin, BB-K8 had a plasma half-life of about 0.8 h which paralleled the urinary excretion rate. Approximately 92% of the dose was excreted as unchanged drug within 6 h of dosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

7
27
0
2

Year Published

1974
1974
1979
1979

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(36 citation statements)
references
References 7 publications
7
27
0
2
Order By: Relevance
“…Studies of pharmacokinetic properties of amikacin in adults have shown the volume of distribution to be 0.25 liter/kg, which is similar to the Vd we found (3,4,6,11,16,18). A previous study of amikacin in pediatric patients revealed a Vd of 0.32 liter/kg, but this higher value probably was due to the inclusion of a large number of patients with cystic fibrosis, who have abnormal weight-to-surface area ratios (25).…”
supporting
confidence: 50%
See 2 more Smart Citations
“…Studies of pharmacokinetic properties of amikacin in adults have shown the volume of distribution to be 0.25 liter/kg, which is similar to the Vd we found (3,4,6,11,16,18). A previous study of amikacin in pediatric patients revealed a Vd of 0.32 liter/kg, but this higher value probably was due to the inclusion of a large number of patients with cystic fibrosis, who have abnormal weight-to-surface area ratios (25).…”
supporting
confidence: 50%
“…A previous study of amikacin in pediatric patients revealed a Vd of 0.32 liter/kg, but this higher value probably was due to the inclusion of a large number of patients with cystic fibrosis, who have abnormal weight-to-surface area ratios (25). The differences in the clinical pharmacology between our pediatric patients and adults can be accounted for by the significantly greater total body clearance of amikacin (131 versus 100 ml/min per 1.73 m2) and shorter half-life (1.24 h in children versus 2.2 h in adults) (3,4,6,11,16,18).…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…Particularly noteworthy is its effect against Pseudomonas aeruginosa and many gentamicin-resistant gram-negative bacilli (1,11,12). Amikacin is derived from kanamycin A and has pharmacokinetic characteristics that are similar to kanamycin (2,3), and animal experiments suggest that it may be comparable to kanamycin with respect to ototoxicity (9). Thus, when clinical trials at this medical center began, administration of the drug was accompanied by careful surveillance for ototoxic effects.…”
mentioning
confidence: 99%
“…the parent compound, kanamycin (3,4,7). The Therapy with amikacin was administered because antibacterial spectrum of amikacin is broader urological surgery was electively sceduled (cases 1, 3, than that of kanamycin, and includes many 4,9) or because febrile clinical illness was present (the sthains of kanamycin, an .nincues many remaining cases).…”
mentioning
confidence: 99%